Kualifikasi Da’i dalam Perspektif Tafsir al-Maraghi dan Relevansinya dengan Kondisi di Indonesia - Zumrodi Zumrodi (AL-BURHAN, 2022)
Islam is a religion that contains the values of mercy and peace. However, these values will not be realized without being socialized and preached. To be able to preach all of this requires a qualified da'i. This study aims to explore Al-Maraghi's assesment in the book